\[\boxed{\text{1187\ (1187).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ (a + 4)^{2} - 2 \cdot (a + 4) + 1 =\]
\[= \left( (a + 4) - 1 \right)^{2} = (a + 3)^{2}\]
\[2)\ (3b + 2)^{2} + 4 \cdot (3b + 2) + 4 =\]
\[= \left( (3b + 2) + 2 \right)^{2} = (3b + 4)^{4}\]
\[3)\ (3y + 8)^{2} + (4y + 6)^{2} + 4y =\]
\[= 25y^{2} + 100y + 100 =\]
\[= (5y + 10)^{2}\]
\[= x^{2} + 26xy + 169y^{2} =\]
\[= (x + 13y)^{2}\ \]
\[\boxed{\text{1187.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[5y - x = 3x - 7y\]
\[12y = 4x\ \ \ |\ \ :4\]
\[3y = x\]
\[3 \cdot 3 = 9\]
\[9 = 9 \Longrightarrow\]
\[\Longrightarrow пересекаются\ в\ точке\ A.\]